Intestinal Parasitic Plethora - SUNILKUMAR.JADA,; KARTHIKA JAYAKUMAR., (International Journal of Pharma and Bio Sciences, 2012)
In an era where anti-helmithic use is more common, it is rare to see any parasite in the stool sample. But in our patients there is a high prevalence rate of parasitic infestation attending our hospital, as proved by the routine stool examination. Aim: To know the prevalence and distribution of the different parasitic infestations in our patients, to identify the ideal method for demonstration of the parasitic ova/cyst. To demonstrate the association of anemia in relation to parasitic infestation. To identify parasitic ova/egg by using Lactophenol cotton blue (LPCB) wet mount. Methods and Material: A total of 300 stool samples were collected and subjected for macroscopic & microscopic examination. Those samples which were negative by wet mount were further subjected for flotation, formal ether sedimentation techniques. For the patients with severe anemia, blood samples were collected and their serum Ferritin levels (ELISA) were assayed. Results: Out of the 300 samples, 129 (43%) were Positive for parasitic infestations which is very high in the current scenario. Our study showed Entamoeba histolytica (30%) Ancylostoma duodenale(22%), Ascaris lumbricoides (16%), Giardia(11%), Taenia(5%), Rhabditiform larva(4%), Trichuris trichiura(2%), Mixed infections(7%), Cyclospora(2%), Chilomastix(1%). Among 129 positive samples, serum Ferritin levels were very low in 88 cases. LPCB wet mount showed better appreciation of morphology than LPCB staining. Conclusions: Simple wet mount is still a reliable technique for screening& LPCB mount for identifying the ova/cyst morphology in stool samples. The Coexistence of anemia and parasitic infestation is augmented in our study by detection of reduced hemoglobin and serum Ferritin levels (P< 0.001). Formal ether is superior to flotation.